Rethinking the Role of Political Parties in Conflict Resolution and Strengthening Democratic Resilience - Nasution, Nanda Rizka Syafriani; Putra, Teddy Chrisprimanata (International Relations Study Program, The Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2026)
Political parties are central actors in democratic systems, influencing policymaking, governance, and the overall stability of political institutions. In post-conflict or politically fragile societies, their role becomes even more critical as they can either facilitate reconciliation and peacebuilding or exacerbate tensions through polarizing strategies. This paper examines the dual role of political parties in conflict resolution and the strengthening of democratic resilience, drawing from theoretical perspectives on democracy, conflict resolution, and institutional stability. The analysis highlights three primary contributions of political parties: acting as mediators in political disputes, designing and promoting reconciliation policies, and fostering inclusive participation in governance. At the same time, the paper identifies persistent challenges such as political polarization, identity-based divisions, corruption, and weak internal democracy. Addressing these issues requires comprehensive reforms, including greater transparency in party operations, stronger legal frameworks, and continuous political education for both members and the public. By aligning the functions of political parties with the principles of peace and democratic governance, societies can enhance their capacity to navigate conflict and sustain long-term democratic resilience. Ultimately, this study argues that political parties are not only instruments of power but also potential architects of sustainable peace and democratic stability.